1998
DOI: 10.1093/ajcn/68.3.531
|View full text |Cite
|
Sign up to set email alerts
|

Aspartame: neuropsychologic and neurophysiologic evaluation of acute and chronic effects

Abstract: Large daily doses of aspartame had no effect on neuropsychologic, neurophysiologic, or behavioral functioning in healthy young adults.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
1
2

Year Published

2001
2001
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(22 citation statements)
references
References 21 publications
0
19
1
2
Order By: Relevance
“…Aspartame also can cause neurochemical changes and affect the levels of neurotransmitters within the brain. In healthy volunteers, plasma phenylalanine (Spiers et al 1998) and aspartate (Møller 1991) concentrations increased significantly after aspartame intake. Møller (1991) has also shown that the intake of aspartame produced a marked and persistent increase of the availability of phenylalanine to the brain, which was not observed after protein intake.…”
Section: Introductionmentioning
confidence: 94%
“…Aspartame also can cause neurochemical changes and affect the levels of neurotransmitters within the brain. In healthy volunteers, plasma phenylalanine (Spiers et al 1998) and aspartate (Møller 1991) concentrations increased significantly after aspartame intake. Møller (1991) has also shown that the intake of aspartame produced a marked and persistent increase of the availability of phenylalanine to the brain, which was not observed after protein intake.…”
Section: Introductionmentioning
confidence: 94%
“…We chose aspartame, a sweetener that does not modify plasma insulin and glucose (Spiers et al 1988;Melchior et al 1991) even at doses close to that used in this study (Carlson and Shah 1989). We first performed a single blind, crossover study with 12 healthy participants to identify the aspartame dose that has the same sweetness as glucose.…”
Section: Determination Of a Placebomentioning
confidence: 99%
“…Phenylalanine and aspartic acid are both amino acids which are found in natural proteins and under normal circumstances are beneficial, if not essential, for health (Woodrow, 1984). It has been reported that aspartame consumption was linked with neurological and behavioral disturbances (Humphries et al, 2008), but most of the results yielded negative or inconclusive correlations (Spiers et al, 1998;Magnuson et al, 2007).…”
Section: Introductionmentioning
confidence: 99%